1999
DOI: 10.1515/jpm.1999.049
|View full text |Cite
|
Sign up to set email alerts
|

MMP/TIMP imbalance in amniotic fluid during PROM: an indirect support for endogenous pathway to membrane rupture

Abstract: Active, TIMP free forms of MMP2 and 9 are increased in the amniotic fluid of women with PROM. These MMPs can degrade the amniochorion basement membranes and other ECM components resulting in PROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
86
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(92 citation statements)
references
References 11 publications
4
86
0
2
Order By: Relevance
“…Fortunato et al (1999a) have reported increased MMP2 levels in the amniotic fluid of women with PPROM, suggesting that MMP2 is implicated in the mechanism responsible for rupture of membranes. In contrast, other reports suggest no changes in amniotic fluid MMP2 levels in women with spontaneous labor (term and preterm) and rupture of membranes (term and preterm) (Maymon et al 2000c(Maymon et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunato et al (1999a) have reported increased MMP2 levels in the amniotic fluid of women with PPROM, suggesting that MMP2 is implicated in the mechanism responsible for rupture of membranes. In contrast, other reports suggest no changes in amniotic fluid MMP2 levels in women with spontaneous labor (term and preterm) and rupture of membranes (term and preterm) (Maymon et al 2000c(Maymon et al , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…All the four TIMPs inhibit MMPs but differ in their affinities for different inhibitor-protease pairs (Brew & Nagase 2010). A number of studies have examined the levels of TIMP1 and TIMP2 in the amniotic fluid and fetal membranes both in term and preterm pregnancy (Athayde et al 1999, Fortunato et al 1999a, Maymon et al 2001, Goldman et al 2003. However, the results are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-1 predominates prior to the onset of contractions as described by Bryant-Greenwood and Yamamoto. FM MMP-2 is constitutive and reportedly does not respond to cytokines or change with PPROM or labor (term or preterm) [Fortunato et al, 1999;Maymon et al, 2001;Xu et al, 2002]. In contrast, both active and latent forms of Bryant-Greenwood et al, 1995;Osmers et al, 1995;Athayde et al, 1999;Vadillo-Ortega et al, 2002).…”
Section: Term Fm Develops a Para-cervical "Weak Zone" Where Rupture Imentioning
confidence: 99%
“…It was also lower than in corresponding area of membranes [20,21]. Another group reported elevated TIMP-1 levels in amniotic fluid samples derived from deliveries complicated with PROM, nevertheless this study did not include MMP-9 assessment or MMP-9/TIMP-1 ratio [22].…”
Section: Discussionmentioning
confidence: 68%